40OSafety and efficacy of everolimus (EVE) plus exemestane (EXE) in postmenopausal women with advanced breast cancer (ABC): Final results from EVEREXES. (24th November 2019) - Im, Y-H; Karabulut, B; Lee, K S; Adhav, A; Park, B-W; Cinkir, H Yesil; Bowles, J; Alfaro, T Delgar; Xue, H L; Kim, S-B
Abstract: Background: Resistance to endocrine therapy in ABC has been linked to the activation of the PI3K/AKT/mTOR pathway. 1 Pivotal phase 3 studies such as BOLERO-2 has shown that treatment (tx) with EVE+EXE (vs EXE+ placebo [PBO]) improves PFS in postmenopausal women with HR+, HER2– ABC progressing on nonsteroidal aromatase inhibitors (NSAIs). 2 However, the BOLERO-2 trial included <10% of the pts from Middle East, Africa, and Asia Pacific nations. The tx outcomes of anticancer agents may vary based on ethnicities, thus it is key to evaluate the safety and efficacy of EVE+EXE in these populations. 3 Here, we report the final safety and efficacy outcomes from the EVEREXES trial. Methods: EVEREXES is a single-arm, phase IIIb study assessing the safety and efficacy of EVE+EXE in postmenopausal pts with HR+, HER2– ABC progressing on/after prior NSAI tx. Pts received EVE (10 mg QD) and EXE (25 mg QD). The primary outcome included safety and tolerability of EVE and the secondary objectives included PFS, ORR and CBR. Results: A total of 235 pts received EVE+EXE therapy. The overall safety analysis were similar to results previously reported for EVE+EXE. AEs were the main reason for dose reduction/interruption. The most common grade 3/4 AEs were stomatitis (10.2%), non-infectious pneumonitis (4.3%), infections (2.1%), hyperlipidemia (1.7%), hypophosphatemia (1.7%) and increased creatinine (1.7%). The table depicts the final efficacy outcomes. Conclusions: The efficacy and safety profile of EVE+EXE in this predominantly Asian patient population is consistent with the BOLERO-2 study, thus validating the use of this combination therapy in Asian pts with HR+, HER2– ABC progressing on/after prior NSAIs. References Baselga J, et al. N Engl J Med 2012;366(6):520-529. Yardley DA, et al. Adv Ther 2013;30(10):870-884. Noguchi S, et al. Breast Cancer 2014;21(6):703714. Clinical trial identification: NCT03176238. Editorial acknowledgement: The authors would like to thank the patients who participated in the EVEREXES study and their families. We acknowledge Susmita Bhattacharjee (Novartis Pharmaceuticals Corporation) for editorial assistance with this abstract. This presentation is the intellectual property of the author/presenter. Legal entity responsible for the study: Novartis Pharmaceuticals Corporation. Funding: Novartis Pharmaceuticals Corporation. Disclosure: B. Karabulut: Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche, Merck Serono, Amgen, Pfizer, Novartis, MSD, BMS, J&J, Astellas, Sanofi, Bayer. K.S. Lee: Honoraria (self): Roche; Non-remunerated activity/ies: Dong-A Pharm; Honoraria (self): Lilly; Honoraria (self): Novartis; Honoraria (self): Pfizer. All other authors have declared no conflicts of interest.